2011
DOI: 10.1186/1479-7364-5-6-569
|View full text |Cite
|
Sign up to set email alerts
|

The role of ALDH2 and ADH1B polymorphism in alcohol consumption and stroke in Han Chinese

Abstract: The genes encoding the enzymes for metabolising alcohol dehydrogenase 1B (ADH1B) and aldehyde dehydrogenase 2 (ALDH2) -- exhibit genetic polymorphism and ethnic variations. Although the ALDH2*2 variant allele has been widely accepted as protecting against the development of alcoholism in Asians, the association of the ADH1B*2 variant allele with drinking behaviour remains inconclusive. The goal of this study was to determine whether the polymorphic ADH1B and ALDH2 genes are associated with stroke in male Han C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…15,27,28 The unpleasant effects may lead to alcohol avoidance and may significantly reduce the prevalence of alcoholism in carriers of the ALDH2*2 allele; this may also indirectly reduce the detrimental influence of ethanol on cardiovascular risk. 29 Yao et al 17 first reported that the frequency of the ALDH2*2 allele in Taiwanese patients with stroke who were also heavy drinkers was significantly lower than those who were not heavy drinkers. The low incidence of the ALDH2*2 allele among heavy drinkers may be directly related to the tendency of Taiwanese patients who have the allele to live an alcohol-avoidant lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…15,27,28 The unpleasant effects may lead to alcohol avoidance and may significantly reduce the prevalence of alcoholism in carriers of the ALDH2*2 allele; this may also indirectly reduce the detrimental influence of ethanol on cardiovascular risk. 29 Yao et al 17 first reported that the frequency of the ALDH2*2 allele in Taiwanese patients with stroke who were also heavy drinkers was significantly lower than those who were not heavy drinkers. The low incidence of the ALDH2*2 allele among heavy drinkers may be directly related to the tendency of Taiwanese patients who have the allele to live an alcohol-avoidant lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in ALDH2 can influence the expression and function of this protein, and consequently increase susceptibility of the individual to a variety of diseases of the central nervous system (Hao et al, 2011;Yao et al, 2011;Li et al, 2015). In a study conducted by Li et al (2015), which included 369 Chinese patients with cerebral infarction and 247 healthy Chinese subjects, it was shown that the A allele in ALDH2 may be a significant risk factor for cerebral infarction in Chinese females .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Li et al (2015), which included 369 Chinese patients with cerebral infarction and 247 healthy Chinese subjects, it was shown that the A allele in ALDH2 may be a significant risk factor for cerebral infarction in Chinese females . Notably, Yao et al (2011) stated that the A allele in ALDH2 is an independent protective variable for patients who have had stroke and have a history of heavy alcohol consumption. Further, in a meta-analysis by Hao et al (2011), it was shown that the GA and AA genotypes in ALDH2 increased the risk of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence indicated that alcohol abuse is sever risk factor for stroke (Gill et al, 1986(Gill et al, , 1991Hillbom et al, 1999;Klatsky et al, 2001;Mazzaglia et al, 2001). ALDH2 polymorphisms play a pivotal role on hypertension (Hasi et al, 2011;Wang et al, 2013;Yokoyama et al, 2013;Hu et al, 2014), heart disease (Gu, Li, 2014;Mizuno et al, 2015) and stroke (Yao et al, 2011;Lai et al, 2012). The single base mutation (ALDH2*2) of ALDH2, the predominant allele in East Asian populations (around 70 %) (Chen, Yin, 2008), is responsible for acute alcohol-flushing reaction in Asians (Crabb, 1990).…”
Section: Discussionmentioning
confidence: 99%